Socio-Economic Impact of Micro Hydro Plants in Bhimeshwar Municipality, Dolakha District, Nepal - Dahal, Ananta Raj (Historical Journal, 2025)
The study highlights the significant potential of Nepal’s 6,000 rivers for hydropower development, which is considered a vital source of energy for the country. This research specially examines the socio-economic impact of micro-hydro projects on rural communities in the Dolakha district, with a focus on assessing whether these projects bring benefits to the surrounding population. Using descriptive research design and primary data collection as the main information source, the study employed descriptive statistics for data analysis. The findings indicate that micro-hydro projects have a substantial positive socio-economic impact on local rural populations. A notable 97 percent of respondents reported that the micro-hydro project increased children’s study time and contributed to improved educational outcomes. In addition, these projects have enhanced agro-processing by saving time and money, thanks to the use of modern technology powered by electricity. Micro-hydro projects have also extended working hours by providing electric lighting for households at night. In conclusion, this study demonstrates that micro-hydro projects significantly improve the socio-economic conditions of rural communities in the sample areas contributing to both educational and economic development.